Parts of Antarctica's King George Island are littered with trash. (26th February 2013) - Kumar, Mohi
Abstract : A report released 7 February by ecologists from Germany's Friedrich Schiller University Jena reveals that parts of King George Island, a logistical hub for international research in Antarctica, are home to open pits of trash, decaying field huts, and other forms of pollution.